The Relationship between Primary Extrauterine Adenosarcoma and the Secondary Müllerian System: Report of a Unique Case Demonstrating Histologic Transition between Benign and Malignant Elements and a Review of the Literature - Liu, MD, PhD, Wei; Axiotis, MD, Constantine A. (North American Journal of Medicine and Science, 2010)
Background: Extrauterine adenosarcomata are thought to arise from pre-existing foci of endometriosis. In 1925 Sampson proposed three criteria for a definitive diagnosis of malignancy arising in endometriosis: (1)histological evidence of endometriosis in close proximity tothe tumour; (2) no other identifiable primary site of malignancy; and (3) histological appearance of the tumour compatible with an origin in endometriosis. In 1953 Scott added a fourth criterion(4) requiring contiguous histological transition of benign endometriosis merging with the malignant component.